The Crying has Stopped: Trends in Yoruba Marriage Ceremonies Practice among Ekiti Peoples, Southwest Nigeria - Idowu, Omowumi Omodunni (Àgídìgbo: ABUAD Journal of the Humanities, 2022)
Marriage is a sacred and noble institution among the Yoruba people of South Western Nigeria. A notable practice during their traditional marriage ceremonies culture is the “Ekun Iyawo” (crying of the new bride) and that of her family before the bride is married off to the groom’s family. The “Ekun Iyawo” is meant for bride on the eve of the wedding ceremony. This cry is an emotionally inspired cry which has nothing to do with hypocrisy. With the performance of “Ekun Iyawo”, a bride is escorted by family and friends to the doorstep of her husband’s home, her new home. However, there has been noticeable change in this practice in Yorubaland, recently. Brides no longer cry and the whole concept of “Ekun Iyawo” is gradually fading away. Using extensive fieldwork in Ekiti state, this study identified that lack of family bond and westernization/’civilization’ through education, religion and new way of doing things are the major factors responsible for non-crying attitude of today’s brides. While its desirability is important, its continuity seems impossible due to the emergence of new generation of parents and mode of parenting.